A Literature Review: Effectiveness of NSAIDs in Osteoarthritis Patients - Adrianto, Madyo; Anak Agung Pradnya Paramitha Vidiani; Puspitaningrum, Anisa Nova; Girsang, Valentina (Science and Community Pharmacy Journal, 2024)
Pain, stiffness, swelling, and decreased joint function are some of the clinical signs of osteoarthritis, a disease that affects numerous anatomical and physiological aspects of joint tissue, cartilage degradation, bone remodeling, and osteophyte development. This literature review's objective is to ascertain the efficacy of NSAIDs in osteoarthritis by searching for journals from PubMed.. The method used was to search for articles through pubmed using the keywords "NSAID", "osteoarthritis", "Therapy" with a filter added for the last 5 years (2019-2024) obtained 103 articles. Then with the keywords "NSAID", "osteoarthritis", "therapy", "efficacy" obtained 71 articles. After analysis, there are 13 journals that can be include into inclusion requirement. NSAIDs preparations are particularly helpful for osteoarthritis therapy, both in knee and hip osteoarthritis. NSAIDs medications in a variety of dose forms, including oral, topical, spray, injection and plaster, are useful in relieving pain in osteoarthritis patients